Stabilizing great-power rivalries - Mazarr, Michael J. 1965-; Charap, Samuel 1980- (RAND Corporation, 2021)
The consensus inside and outside the U.S. government is that the international system is headed for a renewed era of intense and sometimes bitter competition among leading states. The objective of this research was to assess the emerging strategic competitions between the United States and both China and Russia, examine the approaches most likely to preserve long-term stability in these competitions, and draw implications for Army capabilities and posture. To this end, the authors reviewed existing literature on rivalries, identifying variables strongly associated with stability and instability, and, based on that research, developed a framework for assessment of such rivalries. They then applied this framework to historical cases of bilateral rivalries to identify the most important factors. Finally, they leveraged this work to assess the current state of U.S.-Russia and U.S.-China relations. Their assessment suggests that there are serious grounds for concern about the stability of both the U.S.-Russia and U.S.-China rivalries. While certain contextual factors, such as mutual strategic vulnerability, will remain buffers of conflict, many of the warning signs for instability are clearly visible, and the future seems likely to be even more volatile. The report offers recommendations for the U.S. government and the U.S. Army, in particular, to manage this challenging new era of competition. One overarching theme identified is that to ensure stability-and avoid war-the policy response to this intensified great-power competition should be nuanced and go beyond merely bolstering capabilities to counter rivals
Keywords: Geschichte 1950-2019; Rivalität; Gleichgewichtspolitik; Geopolitik; Großmachtpolitik; Balance of power / 21st century; Geopolitics / United States / Forecasting; Great powers / History; Strategy / Research / United States; Balance of power; Geopolitics / Forecasting; Great powers; Strategy / Research; United States; 2000-2099; History